2018
DOI: 10.3390/separations5020029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Pulsed Electric Field on Charge Generation in a Flowing Protein Solution

Abstract: It is known that a charge is generated in water and protein solutions upon their motion; this phenomenon is also observed in analytical systems for atomic force microscopy (AFM)-based fishing. At that, the efficiency of protein fishing correlates with the value of charge, generated upon the motion of the analyzed solution. Earlier, we demonstrated that a pulsed electric field can well be used for the enhancement of the efficiency of AFM-based fishing of low-abundant protein. In this paper, we have demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…It is to be noted that the generation of charge during the flow of water and aqueous solutions along various surfaces [8], as well as changes in the physicochemical properties of water upon its flowing through polymer injectors [9], were long and widely discussed in the literature. In our previous paper [10], we demonstrated that negative pulsed voltage applied to parallel metal plates, between which an injector of the AFM-based fishing system was located, led to an increase in the efficiency of charge generation in the injector. At the same time, we demonstrated that an external AC electric field (with 50 Hz mains frequency, which is often present in biosensor devices) caused an increase in efficiency of charge generation in water flowing through an injector at a low-grade fever temperature (38 • C) [11]; this temperature is higher than that of phase transition of water related with heat capacity (36.6 • C, [9]) and corresponds to a pathology in human.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is to be noted that the generation of charge during the flow of water and aqueous solutions along various surfaces [8], as well as changes in the physicochemical properties of water upon its flowing through polymer injectors [9], were long and widely discussed in the literature. In our previous paper [10], we demonstrated that negative pulsed voltage applied to parallel metal plates, between which an injector of the AFM-based fishing system was located, led to an increase in the efficiency of charge generation in the injector. At the same time, we demonstrated that an external AC electric field (with 50 Hz mains frequency, which is often present in biosensor devices) caused an increase in efficiency of charge generation in water flowing through an injector at a low-grade fever temperature (38 • C) [11]; this temperature is higher than that of phase transition of water related with heat capacity (36.6 • C, [9]) and corresponds to a pathology in human.…”
Section: Introductionmentioning
confidence: 96%
“…The influence of external low-frequency (50 Hz) AC electric field, applied to the injector of the system for AFM-based fishing, has also been studied. Similar to References [10,11,16], this field has been induced by negative AC voltage applied to electrodes, between which the injector was located. The temperature of T = 35 • C was selected due to the following considerations.…”
Section: Introductionmentioning
confidence: 97%
“…With the use of various mechanisms, including those with a radiation-based principle of operation, such interaction can be observed in living cells, as well as in an organism, featuring central nervous system, whose life-sustaining activity is also accompanied by other factors exciting spin transition of water, e.g., electric pulses generated during the functioning of blood circulatory and nervous system due to a triboelectric effect [27,28]. It should be noted that the possibility of enhancement of the parameters of radiation from an enzyme system by means of its stimulation with electric pulses was demonstrated with the example of another heme-containing peroxidase system [29].…”
Section: Discussionmentioning
confidence: 99%
“…Upon the flow of water through the plastic pipe and the tip, an electric charge was generated in it owing to a triboelectric effect [29][30][31][32][33][34][35][36]40,41]. The electric field, organized around the tip, induced charge separation in water.…”
Section: Generation Of Electric Charge and Its Separation In Water Dr...mentioning
confidence: 99%
“…The first way is the application of an external electric field [27]; it is used, for instance, for the electrophoretic separation of proteins [28]. The second way is the use of electrostatic effects occurring in an analytical system upon a motion of a liquid medium [29][30][31][32][33][34][35][36]. This effect of the occurrence of an electric field (that is, the generation of charge) in the analytical system influences its properties.…”
Section: Introductionmentioning
confidence: 99%